Venous Thromboembolism after Joint Replacement in Older Male Veterans with Comorbidity - Kapoor, Alok (2013)
OBJECTIVES: Identifying older adults with comorbidities or poor functional status at high risk for postoperative venous thromboembolism DESIGN: Retrospective cohort study SETTING: Veterans Affairs Medical Center PARTICIPANTS: Older adults who underwent total hip and knee replacement (THR and TKR) from 2002–2009 MEASUREMENTS: Using multivariate logistic regression, we analyzed the independent effect of cardiopulmonary comorbidities and diabetes on VTE. Secondarily, we analyzed functional status expressed in a summary physical component score (PCS) in a subset of patients for whom it was available. RESULTS: There were 23,326 THR and TKR surgeries performed at the VA during the study period. COPD predicted a 25% increase in VTE (OR=1.25, 95% CI 1.06–1.48) CAD, CHF, CVD did not predict increased VTE. Diabetes predicted decreased VTE (OR=0.77 95% CI 0.64–0.92). Very low values of PCS, which was available for 3,169 patients, demonstrated a 62% increase in risk although the effect did not reach statistical significance (lowest versus highest quartile OR =1.62, 95% CI 0.93–2.80). CONCLUSION: COPD predicted a small increase in VTE whereas very low functional status had a larger effect which did not reach statistical significance. More definitive conclusions about the role of these comorbidities and functional status are limited by the constraints of administrative data analysis and sample size available for PCS.